Communication Barriers Between Children and Parents On Whatsapp: A Case Study Of Students at Sindang Elite Junior High School - Selpi Pebriyani; Khaerudin Imawan (Interaction Communication Studies Journal, 2026)
Advances in electronic technology have transformed communication patterns within families, including communication between parents and children. WhatsApp has become an essential tool for maintaining connections when face-to-face communication is not possible. However, the use of WhatsApp in family communication does not always go smoothly and often presents various challenges. This study aims to identify and analyze the forms of communication barriers between parents and children via the WhatsApp app among students at SMPN Unggulan Sindang. This study employs a descriptive qualitative approach, using in-depth interviews with six informants comprising four students and two parents as the data collection technique. Data analysis was conducted by applying Communication Network Theory. The results indicate that the most prominent communication barriers include slow responses, differences in communication styles and digital literacy across generations, and tension between children’s need for privacy and parental control. While WhatsApp facilitates coordination and maintains connectivity, it has not yet fully succeeded in strengthening emotional closeness. These findings suggest that the success of digital communication within the family context depends not only on technical factors but also on mutual agreement and the management of communication patterns between parents and children.